Endoscopic scoring systems for inflammatory bowel disease: pros and cons - Tontini, Gian Eugenio; Bisschops, Raf; Neumann, Helmut (Expert Review of Gastroenterology and Hepatology, 2014)
Endoscopy plays a pivotal role for diagnosis and assessment of disease activity and extent in patients with inflammatory bowel diseases. International guidelines recommend the use of endoscopic scoring systems for evaluation of the prognosis and efficacy of medical treatments. Ideal scoring systems are easy to use, reproducible, reliable, responsive to changes, and validated in different clinical settings in order to guide therapeutic strategies. However, currently available endoscopic scoring systems often appear as complex for routine endoscopy and suffer from insufficient interobserver agreement and lack of formal validation which often limit their use in clinical trials. Here, we describe the role of endoscopic scoring systems in inflammatory bowel diseases focusing on pros and cons in the era of advanced endoscopic imaging and mucosal healing.
EVALuna2:1894